Revisitando os grandes temas do pensamento geopolítico brasileiro - Lima, Wendell Teles de; Oliveira, Ana Maria Liborio; Silva, Iatiçara Oliveira; Fraga, Nilson César (Revista de Geopolítica, 2016)
Resumo